Pilot study: Association between Helicobacter pylori in adenoid hyperplasia and reflux episodes detected by multiple intraluminal impedance in children - Katra, R; Kabelka, Z; Jurovcik, M; Hradsky, O; Kraus, J; Pavlik, E; Nartova, E; Lukes, P; Astl, J (International journal of pediatric otorhinolaryngology, 2014)
OBJECTIVES: The aim of this pilot study was to investigate an association between laryngopharyngeal reflux detected by combined multiple intraluminal impedance and pH monitoring and Helicobacter pylori in adenoid hyperplasia detected with real time polymerase chain reaction (PCR). METHODS: The study group consisted of 30 children (median age 5.34 years) with extraesophageal symptoms of gastroesophageal reflux disease with adenoid hyperplasia. All children underwent adenoidectomy with subsequent PCR detection of H. pylori DNA in the tissue and multiple intraluminal impedance and pH monitoring. The most proximal impedance sensor was located 1cm caudal to the entrance of the oesophagus. RESULTS: We found significant differences in the number of reflux episodes among patients with PCR positivity (median 35) and negativity (median 0) of H. pylori (p-value of Mann-Whitney U-test 0.0056). Patients with PCR positivity of H. pylori had significantly more reflux episodes reaching the upper oesophageal sphincter (p-value of Mann-Whitney U-test 0.023). The absence of reflux episode was the only independent factor for PCR negativity of H. pylori in the multiple logistic regression model. CONCLUSIONS: These results support the hypothesis that reflux episodes reaching the upper oesophageal sphincter may play an important role in the transmission of H. pylori into lymphoid tissue of the nasopharynx and thus may contribute to adenoid hyperplasia in children.
Keywords: Multiple intraluminal impedance; adenoidy; hyperplazie; DNA bakterií; Laryngopharyngeal and gastroesophageal reflux; Humans; dítě; PCR; Child; Female; Laryngopharyngeal Reflux; lidé; Hyperplasia; Esophageal pH Monitoring; pilotní projekty; Pilot Projects; monitorování jícnového pH; předškolní dítě; DNA, Bacterial; Adenoids; laryngofaryngeální reflux; ženské pohlaví; Helicobacter Infections; Helicobacter pylori; Male; infekce vyvolané Helicobacter pylori; Real-Time Polymerase Chain Reaction; elektrická impedance; mužské pohlaví; Adenoid hyperplasia; Child, Preschool; Electric Impedance; kvantitativní polymerázová řetězová reakce